(untitled) (Journal of Business Management and Accounting, 2014)
This paper provides an idealistic conceptual framework for Research & Development (R&D) evaluation. R&D is very important in higher level decision making. In Malaysia, though the spending is on increasing term, only a small proportionate of Gross Domestic Product (GDP) is allocated to fund R&D as compared to the required tasks in the vast fields of research. A lot of efforts were spent in R&D, the undertakings of which should be monitored and well-funded to ensure the results of the research are considered in making decisions that could be shared, implemented, improvised, and evaluated. Public research which focuses more on educational know-how in the development of human resource/human capital could be assimilated in R&D of private sectors which focus more on scientific, technology, material handling, and information and communication technology (ICT). The more advances occur in science and technology fields, the demand for manpower in the related fields would increase. In spite of this, any improvement from the implemented research result could not be assured even with functional R&D systems if there is no constant evaluation and post decision valuation. The collaboration of public-private R&D institutions would generate a new breed of innovative entrepreneurs that could assist Malaysia to achieve developed nation status as set out in Vision 2020. The outcome of this paper is a proposed model of the Malaysian R&D evaluation in public agencies, private sectors, and universities to construct an idealistic R&D decision evaluation framework for future application. The model presents the interconnected interactions that take place within the stakeholders circle in R&D network. Basically, the model is drawn up under the principle that virtually there are balanced interactions and the interested parties are inter-related.